MATH SOLVE

3 months ago

Q:
# solve the system .....................β

Accepted Solution

A:

Answer:x = 1 y = 2z = - 3Step-by-step explanation:z=-2+3x - 2y Rearrange: x + 4y3z = 18 2xy-3z9 Substitute into one of the equations:[x+4y-3(-2+ 3x β 2y) = 182x-y-3(-2+3x-2y) = 9Apply Multiplicative Distribution Law: x + 4y + 6-9x+6y=18[2x-y+6-9x+6y=9 Rearrange unknown terms to the left side of the equation: x + 4y - 9x+6y= 18-6 2xy +6 9x+6y=9Calculate the sum or difference:x + 4y - 9x+6y= 122xy + 6-9x+6y=9Combine like terms: -8x+10y = 12 -7x+5y+6=9 Reduce the greatest common factor on both sides of the equation: - 4x + 5y = 6 -7x + 5y + 6 = 9 Rearrange unknown terms to the left side of the equation: -4x + 5y = 6 -7x + 5y = 9-6Subtract the two equations: -4x+5y-(-7x+5y)= 6-(9-6)Remove parentheses: - 4x + 5y + 7x - 5y = 6β9+6Cancel one variable: - 4x + 7x = 6 - 9 + 6 Combine like terms: 3x = 6 - 9 + 6Calculate the sum or difference: 3x = 3 Divide both sides of the equation by the coefficient of variable: x = 3/3 Calculate the product or quotient: x = 1 Substitute into one of the equations: -4+5y = 6Rearrange unknown terms to the left side of the equation: 5y = 6 + 4 Calculate the sum or difference: 5y = 10 Divide both sides of the equation by the coef ficient of variable: y = 10/5 Calculate the product or quotient: y = 2The solution of the system is: x = 1 y = 2 Substitute into one of the equations: z = - 2 +3-2x2 Calculate the product or quotient: z = - 2 + 3 - 4Calculate the sum or difference: z = 1 - 4 Calculate the sum or difference: z = - 3 x = 1 y = 2 -3 The solution of the system is:x = 1y = 2z = - 3